Governance And The Challenge Of Socio-Economic Development In Nigeria. - Ojo, Patrick Oluwole; Aworawo, Friday; Elizabeth, IfedayoTolu (Journal of Sustainable Development Law and Policy, 2025)
Various factors are said to be responsible for Nigeria’s current status as an underdeveloped country. These range from historical colonial experience, political instability, the monoculture nature of the national economy, and the persistent lack of commitment to focused development strategies on the part of the political elites. The most popular among the prescriptions for tackling the phenomenon of underdevelopment emphasized macroeconomic policies, economic diversification, transparency and accountability in governance and even direct distribution of resource proceeds to the general population. These solutions have not been able to adequately address Nigeria’s development challenges. However, the crucial role of the regulatory institutions, especially their oversight functions, has arguably been the missing link in establishing the complimentary relationship between governance and development in Nigeria. This paper discusses the importance of governance institutions as a fundamental determinant of robust and sustainable social and economic development in Nigeria.